Synthesis of Oxazolone and Imidazolone Derivatives in Presence of H2O2 Promoted Fly Ash as a Novel and Efficient Catalyst - S. Fozooni; H. Khoshdast; H. Hassani; H. Hamidian (Journal of Sciences, Islamic Republic of Iran)
A new catalyst was prepared by promoting fly ash with hydrogen peroxide. The catalytic activity of H2O2 promoted fly ash (HPFA) was evaluated by synthesis 5(4H)-oxazolone and imidazolone derivatives under solvent free conditions. The possible mechanisms of synthesis reactions were also suggested. These proposed methods benefit in terms of low-cost catalyst, high yields, ease of workup, survival of different functional groups, reusability of the catalyst and short reaction time. These advantages render HPFA to be a promising catalyst for synthesis of organic materials.